Standard specification for Weight [Mass] of Coating on Iron and Steel Articles with Zinc or Zinc-Alloy Coatings (American Society for Testing and Materials, 2009)
This test method covers procedures for determining the weight [mass] of coating on iron or steel sheet, wire, and other articles in which the coating is zinc or a zinc alloy, such as zinc-5 % aluminum (including zinc-5% aluminum mischmetal and zinc-5% aluminum-0.1% magnesium) or 55% aluminum-zinc. In the body of this test method, reference to zinc coating shall be interpreted to also include zinc alloy coating except where specifically stated otherwise.